PENGARUH MEDIA RITATOON BERBASIS KEARIFAN LOKAL TERHADAP KEMAMPUAN MENGUNGKAPKAN BAHASA ANAK USIA 5-6 TAHUN - Pebby Pebrianti; Nyimas Muazzomi; Winda Sherly Utami (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2025)
This research investigates how ritatoon media rooted in local wisdom influences the linguistic expression capabilities of 5-6 year old children at TKIT Pelita Dektora Bagan Pete, located in Alam Barajo District, Jambi City. The methodology employed was a quantitative experimental design using Pre-Experimental approach through One-Group Pretest-Posttest Design. Fourteen children from class B1, aged 5-6 years, participated as research subjects. Data collection was conducted via observational methods utilizing checklist instruments to evaluate children's linguistic expression competencies. Findings revealed a substantial impact of ritatoon media on enhancing children's language expression skills. Statistical analysis demonstrated t-calculated (24.213) exceeded t-table (2.160) with significance level 0.000 < 0.05, confirming H0 rejection and H1 acceptance. Cohen's formula for effect size yielded 4.21, indicating a robust influence. Pre-intervention mean scores reached 7.36, while post-intervention scores achieved 16.57, demonstrating an improvement of 9.21 points. The study establishes that ritatoon media incorporating local wisdom elements successfully enhances linguistic expression abilities among 5-6 year old children.